EFEKTIFITAS PEMBERIAN PIJAT TUINA DALAM MENINGKATKAN NAFSU MAKAN DAN GIZI PADA ANAK STUNTING (LITELATURE REVIEW) - Widianti, Sherly; Murtiningsih (LPPM STIKes Mitra Adiguna, 2025)
Stunting is a nutritional problem that is still a big challenge in various countries, including Indonesia. Based on data from the World Health Organization (WHO), around 22% of Indonesian children experience stunting, which can have long-term impacts on health, cognitive development and productivity in the future. One of the main factors causing stunting is a lack of adequate nutritional intake, which is often related to low appetite in children (WHO, 2018). This research aims to determine the effectiveness of giving tuina massage in increasing appetite and nutrition in stunted children. Search results from the database found 10 articles that met the research criteria. From several studies it was found that the effectiveness of giving tuina massage in increasing appetite and nutrition in stunted children is all effective and successful in increasing children's weight and appetite. By knowing the effectiveness of giving tuina massage in increasing appetite and nutrition in stunted children, it is hoped that hospital management will find a solution in handling stunting problems using non-pharmacological techniques so that health problems can be resolved by doing tuina massage.